The Influence of CLL on EFL Learners’ Speaking Skill - Muhammad Ilyas (J-SHMIC : Journal of English for Academic, 2018)
Some students in the university got some difficulties to express their ideas, especially expressing in foreign language such as English. How to start comunication and interaction sometime need someone to stimulate. The phenomenon often encountered in various levels of education even to the students college. The students tended to be very subjective towards topics, their peer or even partner. In the teaching and learning process, the teacher not only transfer the information to the students but also facilitate the students, stimulate to learn English and provide the technique suitable with the students’ need. Teaching English language might be carried out through several techniques, one of them was CLL (Community Language Learning). In this technique, students were treated as clients who could express their problems to the counselor as well as in the community. In addition, the teacher played the role of translator to help students express themselves using English. This means that learners had enough opportunities to speak without worrying about their limitations in using English. The results showed that CLL helped students to express ideas systematically. The ideas were organized well, understandable, and standardized. In addition, CLL improved the result of students’ score in speaking skill. The mean score increased from 54.74 in pre-test to 72.86 in post-test. It means that CLL gave good influence on students’ speaking skill.